Beyond Cyberbullying: Investigating When and How Cybervictimization Predicts Suicidal Ideation. - Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes; Neto, Félix (Sage, 2020)
Cybervictimization is a public health concern in adolescence. Victims of cyberbullying may present with important short- and long-term sequelae. Specifically, past research has demonstrated positive associations between being cybervictimized and risk of suicide among adolescents. Nonetheless, the underlying mechanisms that may mediate or moderate this relationship remain unclear. The present research examined perceived stress as a mediator and forgiveness as a moderator to explore the relationship between cybervictimization and suicidal ideation. Specifically, vengeance, avoidance, and benevolence motivations, as a means of measuring forgiveness experienced, were analyzed as moderators in the relations between cybervictimization and suicidal ideation. The sample included 1,821 adolescents (954 girls) who ranged in age from 12 to 17 years from nine centers. Adolescents’ self-reported perceived stress levels, cybervictimization, and forgiveness were collected. A mediation and a moderated mediation analyses were used to explore the aim of the present study. Results suggest that, after controlling for sex and age, perceived stress partially mediates the association between cybervictimization and suicidal ideation. Furthermore, the mediation effects of perceived stress were independently moderated by vengeance and avoidance. Thus, revenge and avoidance might intensify the adverse impact of perceived stress on suicidal ideation. These results highlight how and when cybervictimization is related to suicidal ideation. We discuss the results in relation to previous research and consider their practical implications. These findings suggest that adolescents’ perceived stress, together with vengeance and avoidance motivations, may be key targets for prevention and intervention programs dealing with cybervictimization. This highlights the need to implement treatment and prevention programs focused on decreasing such motivations.
Copyright de los autores
Keywords: Estrés (Psicología); Ciberacoso; Suicidio - Factores de riesgo; Adolescentes - Psicología; Cybervictimization; Perceived stress; Suicide risk; Revenge; Avoidance; Adolescence